2016
DOI: 10.1016/j.scr.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic differentiation of human pluripotent stem cells in miniaturized format suitable for high-throughput screen

Abstract: The establishment of protocols to differentiate human pluripotent stem cells (hPSCs) including embryonic (ESC) and induced pluripotent (iPSC) stem cells into functional hepatocyte-like cells (HLCs) creates new opportunities to study liver metabolism, genetic diseases and infection of hepatotropic viruses (hepatitis B and C viruses) in the context of specific genetic background. While supporting efficient differentiation to HLCs, the published protocols are limited in terms of differentiation into fully mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 21 publications
1
102
1
Order By: Relevance
“…The main challenges are to obtain HLCs exhibiting a mature and homogeneous level of differentiation and maintain their differentiation status in vitro . Here, we optimized our previous method to differentiate stem cells more efficiently into a homogeneous population of mature HLCs capable of retaining their phenotype for a prolonged period of time [8]. HLCs were obtained from hESCs or iPSCs (non-colony type monolayer-adapted) through a three-step differentiation protocol (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenges are to obtain HLCs exhibiting a mature and homogeneous level of differentiation and maintain their differentiation status in vitro . Here, we optimized our previous method to differentiate stem cells more efficiently into a homogeneous population of mature HLCs capable of retaining their phenotype for a prolonged period of time [8]. HLCs were obtained from hESCs or iPSCs (non-colony type monolayer-adapted) through a three-step differentiation protocol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Non-colony monolayer type culture human embryonic stem cells (hESCs) H9 and iPSCs SC3D cell line have been described previously [7, 8] and were maintained on growth factor-reduced (GF(-)) Matrigel (0.4 mg/ml)(Corning, NY, USA) in mTeSR1 (StemCell Technologies, Vancouver, Canada). Cells were routinely passed 1 in 8 every 5–6 days with Accutase (Life Technologies, Frederick, USA) and reseeded with mTeSR1 medium in presence of 10 µM of Rock Inhibitor Y-27632 (Millipore, Billerica, USA) as described before [7, 8]. …”
Section: Methodsmentioning
confidence: 99%
“…We adapted a recently published protocol that described the derivation of functional hepatocyte-like cells from human embryonic stem cells (ESCs) and iPSCs. 27,28 Although the kinetics of hepatic differentiation of RhiPSCs was similar to that of human iPSCs, we found that hypoxic culture (5% O 2 ) during definitive endoderm induction was necessary in RhiPSC differentiation ( Figure S7). After 4 days of differentiation, pluripotent genes were downregulated and RhiPSCs generated homogeneous definitive endoderm, which expressed SOX17 and FOXA2.…”
Section: Endodermal Differentiation From Edited Rhipscsmentioning
confidence: 88%
“…After 4 days, cells were transferred to a normoxic incubator and further differentiated to hepatoblasts in medium with 100 ng/ml hepatocyte growth factor and 1% DMSO for 8 days, as previously described. 27,28 Finally, cells were pushed toward hepatocyte-like cells with the addition of 10 À7 M dexamethasone for 3 additional days. At each time point, cells were analyzed by Taqman RT-qPCR and immunostaining as previously described.…”
Section: Hepatic Differentiationmentioning
confidence: 99%
“…Researchers’ ability to generate iPSCs from patients with inborn errors of hepatic metabolism and to use them to produce cells with hepatocyte characteristics in culture offers the possibility of using the cells for drug discovery 44 .…”
Section: Using Ipscs As a Platform To Identify Pharmaceuticals For Thmentioning
confidence: 99%